I was here - Forman, Gayle (New York, New York Viking, an imprint of Penguin Group (USA), 2015)
In an attempt to understand why her best friend committed suicide, eighteen-year-old Cody Reynolds retraces her dead friend's footsteps and makes some startling discoveries
Includes bibliographical references
1
Keywords: Best friends -- Fiction; Friendship -- Fiction; Grief -- Fiction; Mystery and detective stories; Suicide -- Fiction; Washington (State) -- Fiction